ICT DEVELOPMENT AND EXPORT VOLUME IN UZBEKISTAN: REGIONAL PANEL DATA ANALYSIS (2015–2024) - Sadriddinov Ulugbek Jaloliddin ugli (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article quantitatively studies the impact of the Information and Communication Technology (ICT) Development Index (IDI) on export volume based on panel data for 15 administrative-territorial units of Uzbekistan for 2015–2024. The annual export volume of the regions (in million US dollars, log) was taken as the dependent variable, and the IDI index calculated based on the ITU methodology was selected as the main independent variable. GDP (in US dollars, log), investment volume (log), urbanization level, and trade openness indicators were included as control variables. Four models were used, including random effects (RE), fixed effects (FE), and their robustness versions. A total of 150 observations were analyzed. The results showed that the IDI index had a statistically significant positive effect only in the fixed effects model (β=1.513, p<0.05), while in other models this effect was not statistically confirmed. GDP and investment had a strong positive effect in all models, while urbanization was not significant in any model. Trade openness was significant in the RE and FE models, and partially significant in the robustness versions. The results of the study show that the impact of ICT development on export volume is complex and not one-sided in the context of the regions of Uzbekistan, and relevant policy conclusions are drawn.